STUDI ETNOFARMASI TUMBUHAN OBAT SEBAGAI ANTIHIPERTENSI DI DESA PATTALLASSANG, KECAMATAN PATTALLASSANG KABUPATEN GOWA - Fadhilah, Putri Nur; Malik, Abd.; Hasnaeni, Hasnaeni (PHARMACY UMI JOURNAL SYSTEM, 2025)
Hypertension remains a prevalent global health concern and leading cause of mortality worldwide. In Pattallassang Village, traditional medicine utilizing medicinal plants persists as a common therapeutic approach for hypertension management. This study aimed to systematically identify, document and evaluate the ethnomedicinal knowledge of local communities regarding antihypertensive plants. Employing a descriptive observational design, data were collected through structured interviews and questionnaires administered to 100 respondents. The investigation identified 31 plant species utilized as antihypertensive agents, with the most prevalent being Allium sativum (garlic), Cucumis sativus (cucumber), Annona muricata (soursop leaves), Apium graveolens (celery), and Syzygium polyanthum (bay leaf). The leaves were boiled and the decoction was consumed as herbal infusions. Quantitative analysis using Use Value (UV) indices revealed Allium sativum as the most utilized species (UV=0.41), followed by Cucumis sativus (0.26), Apium graveolens (0.16), and Annona muricata (0.15). These findings demonstrate the preservation of significant ethnobotanical knowledge within the community regarding plant-based hypertension treatment. The study highlights the need for: (1) conservation efforts to protect this traditional knowledge, and (2) further pharmacological research to validate the therapeutic efficacy of these plants. Keywords: Ethnopharmaceutical; medicinal plants; Hypertension; Traditional Medicine; Pattallassang Village